A formação docente: PIBID e o estágio supervisionado - Rodrigues, Regina Célia Cola (2015)
This study aimed to analyze the concepts that guide the Curricular Supervised Internship and the Institutional Program Initiation Grant to Teaching (in Portuguese PIBID) while teaching initiation activity. We aim to understand: can the PIBID while initiation activity teaching be considered as Supervised? Therefore, qualitative approach was used through desk research, literature studies on initial teacher education and official documents by analyzing the concepts and actions that guide the Curricular Supervised Internship and PIBID. The theoretical and political aspects that influence directly or indirectly the teacher training processes were considered; teacher education policy; the legal instruments underlying the PIBID and Supervised. The locus of the work is the Faculty of Education and the PIBID developed by PUC/SP University. This research revealed that the PIBID and Curricular Supervised Curricular Supervised have similarities regarding the structuring principles: connection between theory and practice, research and reflection on the strategy and the action approximation of IES training institutions and Public Schools of Basic Education and demystification of superiority of culture over each other and raising the quality of academic activities in undergraduate programs. On the other hand, the objective conditions under which differentiate them: the Curricular Supervised Internship have less time and bond with schools and basic education teachers and relies primarily by observation. While in PIBID the collective and collaborative work is favored from its planning to its assessment, involving not only the teachers as teachers of IES and Basic Education Schools. In addition, the PIBID presents itself as a possibility for few, being a scholarship program that does not include all training nor the teachers involved